2012
DOI: 10.3109/0142159x.2012.716177
|View full text |Cite
|
Sign up to set email alerts
|

Construct validation of progress testing to measure knowledge and visual skills in radiology

Abstract: We found support for the reliability and construct validity of the DRPT. However, assessment on visual skill development needs further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
2
30
0
2
Order By: Relevance
“…Regarding construct validity, we only found significant differences in mean test scores between lower training years. This finding had been reported by the authors and others previously [5,16]. The reliability per year group is inconsistent.…”
Section: Discussionsupporting
confidence: 58%
“…Regarding construct validity, we only found significant differences in mean test scores between lower training years. This finding had been reported by the authors and others previously [5,16]. The reliability per year group is inconsistent.…”
Section: Discussionsupporting
confidence: 58%
“…How expertise in radiology develops and which factors influence its development is largely unknown (10,11). In a previous cross-sectional study (12), we found that scores on knowledge and image questions in a radiology test differ between 1st-, 2nd-, and 3rd-year residents, but were similar for residents in postgraduate year 4 and 5. This suggested that knowledge and image interpretation skill development slows down during residency; however, this was not evaluated in a longitudinal study that tracked individual score development over time.…”
Section: Implication For Patient Carementioning
confidence: 79%
“…We hypothesized that development of radiologic knowledge and image interpretation skill show a curvilinear growth (12). We also hypothesized that image interpretation skill develops faster in a nonacademic training environment because of higher reading volumes than in academic hospitals (13).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations